Large group interventions : engaging the whole system for rapid change - Bunker, Barbara Benedict (Jossey-Bass San FranciscoUS, 1997)
Defines Large Group Intervention (LGI) and lists advantages the approach offers. Outlines the theoretical framework/historical development of LGIs; presents methodologies for employing them; and uses real-life examples and case studies as illustrations. Presents 4 methods that focus on the role/activities of employees in planning the future direction of their workplace. Discusses 4 methods that focus on the active participation of the workforce in problem solving, decision making, and eventually redesigning the work process. Presents 4 methods using the LGI approach to address day-to-day work-related issues. Explores the similarities and differences within the groups of methods presented.